A wealth tax on corporations' stock. (4th August 2022) - Saez, Emmanuel; Zucman, Gabriel
Abstract: We propose to institute a new tax on corporations' stock shares for all publicly listed companies and large private companies headquartered in G20 countries. Each of these companies would have to pay 0.2% of the value of its stock in taxes each year. As the G20 stock market capitalization is around 100% of world GDP, the tax would raise approximately 0.2% of world GDP in revenue. Because stock ownership is highly concentrated among the rich, this tax would be progressive. The tax could be paid in kind by corporations (by issuing new stock) so that the tax does not raise liquidity issue nor affect business operations. In today's globalized and fast-moving world, companies can become enormously valuable once they establish market power, even before they start making large profits (e.g., Amazon and Tesla). This tax would make them start paying taxes sooner than standard income taxes.